2017
DOI: 10.1016/j.still.2017.04.003
|View full text |Cite
|
Sign up to set email alerts
|

Long-term N fertilization and conservation tillage practices conserve surface but not profile SOC stocks under semi-arid irrigated corn

Abstract: A B S T R A C TNo tillage (NT) and N fertilization can increase surface soil organic C (SOC) stocks, but these gains are frequently not observed through the soil profile and could be subject to loss through subsequent tillage events. We evaluated a long-term irrigated continuous corn no-tillage (NT) and N rate study near Fort Collins, CO that was split into continuous NT or strip till (ST) treatments after five years. We measured grain and residue yields yearly, and SOC and particulate organic matter C (POM-C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 50 publications
2
31
0
1
Order By: Relevance
“…While subgroup analysis suggested that residual removal did not affect SOC beyond the 0–30 cm profile, meta‐regression analysis indicated that reduction in SOC stock was larger in the 0–150 cm interval than the 0–15 or 0–30 cm interval. In fact, some field experiments (Huang, Yang, Huang, & Ju, ; Stewart, Halvorson, & Delgado, ) found that changes in tillage and C input can affect deep SOC, probably because deep SOC can be susceptible to decomposition and priming from the addition of new labile organic C. For instance, a 13 year study found that adoption of NT reduced corn‐derived C in layers deeper than 30 cm, which in turn reduced SOC (Stewart et al, ). Follett, Vogel, Varvel, Mitchell, and Kimble () reported that more than 50% of the increase in SOC was below the 30 cm depth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While subgroup analysis suggested that residual removal did not affect SOC beyond the 0–30 cm profile, meta‐regression analysis indicated that reduction in SOC stock was larger in the 0–150 cm interval than the 0–15 or 0–30 cm interval. In fact, some field experiments (Huang, Yang, Huang, & Ju, ; Stewart, Halvorson, & Delgado, ) found that changes in tillage and C input can affect deep SOC, probably because deep SOC can be susceptible to decomposition and priming from the addition of new labile organic C. For instance, a 13 year study found that adoption of NT reduced corn‐derived C in layers deeper than 30 cm, which in turn reduced SOC (Stewart et al, ). Follett, Vogel, Varvel, Mitchell, and Kimble () reported that more than 50% of the increase in SOC was below the 30 cm depth.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms of deep soil change are not well measured or understood. Possible explanations include leaching of dissolved organic carbon, changes in C input from upper soil, bioturbation caused by earthworms, and changes in root distribution (Kinoshita, Schindelbeck, & Es, 2017;Stewart et al, 2017).…”
Section: F I G U R E 1mentioning
confidence: 99%
“…The adoption of NT recovers SOC, although only partially offsetting initial losses from the soils of native ecosystems (Luo, Wang, & Sun, 2010; Kopittke, Dalal, Finn, & Menzies, 2017). However, NT experiments are relatively recent (<50 years) and generally assess agroecosystems with low‐ to moderate‐inputs in order to replicate regional agricultural practices (Bayer, Martin‐Neto, Mielniczuk, Pavinato, & Dieckow, 2006; Boddey et al, 2010; Corbeels et al, 2016; Follett, Jantalia, & Halvorson, 2013; Martínez et al, 2016; Olson, Ebelhar, & Lang, 2013; Poffenbarger et al, 2017; Poirier et al, 2009; Stewart, Halvorson, & Delgado, 2017). Very few studies were able to assess long‐term SOC dynamics in high‐yield agroecosystems (Cook & Trlica, 2016; Grassini & Cassman, 2012; Grassini, Specht, Tollenaar, Ciampitti, & Cassman, 2015; Walia, Baer, Krausz, & Cook, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have found microbial processing to be the key transformation in efficient soil C stabilization (Cotrufo et al, 2015). Irrigation increases plant productivity and should enhance soil C storage (Lal et al, 1998), but many studies find that irrigated systems rapidly cycle soil C rather than store enhanced plant productivity in the form of SOC (Verma et al, 2005;Denef et al, 2008;Gillabel et al, 2007;Stewart et al, 2017). Microbial transformations are particularly important in irrigated production systems where stabilized C may be more susceptible to C losses through subsequent management changes (Stewart et al, 2018).…”
Section: Core Ideasmentioning
confidence: 99%